First Principles Study on the CO Oxidation on Mn-Embedded Divacancy Graphene - Jiang, Quanguo; Zhang, Jianfeng; Ao, Zhimin; Huang, Huajie; He, Haiyan; Wu, Yuping (Frontiers in Chemistry, 2018)
The CO oxidation mechanism on graphene with divacancy (DG) embedded with transition metal from Sc to Zn has been studied by using first principles calculations. The results indicate that O2 molecule is preferentially adsorbed on Sc, Ti, V, Cr, Mn and Fe-DG, which can avoid the CO poisoning problem that many catalysts facing and is beneficial to the CO oxidation progress. Further study indicates that Mn-DG shows the best catalytic properties for CO oxidation with consideration of both Eley-Rideal (ER) and Langmuir-Hinshelwood (LH) oxidation mechanisms. In the ER mechanism, the energy barrier for the primary step (CO free + O2 pre-adsorbed -> OOCO) is 0.96 eV. In the LH mechanism, the energy barrier for the rate limiting step (CO adsorbed + O2 adsorbed -> OOCO) is only 0.41 eV, indicating that LH mechanism is more favourable for CO oxidation on Mn-DG. Hirshfeld analysis shows that the charge distributions of O2 and CO molecules is tuned by the embedded Mn atom, and the charge transfer from the embedded Mn atom to the adsorbed molecules plays an important role for the CO oxidation. The result shows that the Mn-embedded divacancy graphene is a noble-metal free and efficient catalyst for CO oxidation at low temperature.